Bioactivity and safety of B7‐H3‐targeted chimeric antigen receptor T cells against anaplastic meningioma. Issue 6 (12th June 2020) - Tang, Xin; Liu, Fujun; Liu, Zhiyong; Cao, Yi; Zhang, Zongliang; Wang, Yuelong; Huang, Jianhan; Fan, Shuangming; Zhao, Shasha; Chen, Yaxin; Li, Gaowei; Wang, Shan; et al.
Abstract: Objective: We conducted a first‐in‐human study to evaluate the bioactivity and safety of B7‐H3‐targeted chimeric antigen receptor (CAR) autologous T cells for treating recurrent anaplastic meningioma. Methods: Tumor tissues from a patient with recurrent anaplastic meningioma were evaluated for B7‐H3 expression. B7‐H3‐targeted CAR‐T cells were delivered into the intracranial tumor resection cavity using an Ommaya device at a maximum dose of 1.5 × 10 7 cells. Magnetic resonance imaging (MRI) screening and multiple serum indexes were regularly monitored. The patient received surgical intervention after three‐cycle infusions, allowing analysis for CAR‐T‐cell infiltration and target antigen expression in post‐CAR‐T therapy tumor tissues. Results: Immunochemical analysis demonstrated high and homogeneous B7‐H3 expression in tumor samples. MRI results indicated that the tumor near the delivery device was relatively stable compared with the rapid progression of tumors distant from the device. We found CAR‐T‐cell trafficking to regions of B7‐H3 + tumor tissues near the device, but not to tumor tissues distant from the device. Decreased B7‐H3 expression was observed near the region of CAR‐T‐cell infiltration after therapy. The intracavitary delivery of B7‐H3‐targeted CAR‐T cells was well‐tolerated and not associated with any toxic effects of grade 3 or higher. Conclusion: Our results suggested that although intracavitary administration of B7‐H3‐targeted CAR‐T cells was safe and resulted in local bioactivity, addressing antigen loss and CAR‐T‐cell trafficking may further enhance the applications of B7‐H3‐targeted CAR‐T‐cell therapy. Abstract : We present a first‐in‐human B7‐H3 (CD276)‐targeted CAR‐T‐cell pilot study for the treatment of recurrent anaplastic meningioma and evaluated the bioactivity and safety of this approach. We provide the evidence of safety and anti‐tumor response of local administration autologous B7‐H3‐targeted CAR‐T cells and have established the foundation for further development of B7‐H3‐targeted CAR‐T‐cell therapy.